Real-time imaging of brain areas involved in the generation of spontaneous skin sympathetic nerve activity at rest - James, Cheree; Henderson, Luke; Macefield, Vaughan G. (NeuroImage (Orlando, Fla.), 2013)
In thermoneutral conditions resting skin sympathetic nerve activity (SSNA) is related to the level of arousal and emotional state. The brain regions responsible for the generation of spontaneous SSNA are not known. In the present study we used concurrent recordings of SSNA and brain activity in awake humans to identify cortical and subcortical areas involved in the generation of spontaneous SSNA in 13 healthy subjects. Blood oxygen level dependent signal intensity increases covaried with SSNA in the left thalamus in the region of the ventromedial nucleus, the left posterior and right anterior insula, the right orbitofrontal cortex, the right frontal cortex, and bilaterally in the mid-cingulate cortex and precuneus. Functional connectivity analysis revealed a strong positive coupling between the right orbitofrontal cortex and the right anterior insula. Furthermore, signal intensity changes within the precuneus were temporally coupled to the left anterior and posterior insula, cerebellum, cingulate cortex and thalamus. It has been hypothesized that these brain regions monitor the internal state of the body and may regulate emotional state changes. Our results show that the activities within these regions are also correlated to spontaneous fluctuations in SSNA. ► Recordings were made of skin sympathetic nerve activity concurrently with fMRI. ► Signal intensity in several areas covaried with skin sympathetic nerve activity. ► These included the insula, orbitofrontal, frontal, midcingulate and precuneus. ► Signal intensity within precuneus was temporally coupled to the insula. ► Both of these areas are believed to monitor the internal state of the body.